Light metal amides for hydrogen storage and ammonia decomposition - Makepeace, J (2014)
Hydrogen has long been touted as an alternative fuel which could form the basis of a sustainable energy system: the hydrogen economy. This thesis advances the application of light metal amide materials in the realisation of this transformative potential. One of the most vexing technical challenges to the widespread adoption of hydrogen in transportation applications is its low volumetric energy density, which makes the storage of a sufficient amount of hydrogen in a vehicle very difficult. In their conventional application, light metal amides (M(NH2)x),where M is a Group I or II metal) have been promoted as a means of storing large quantities hydrogen in the solid state, significantly increasing this energy density. This thesis highlights the impressive characteristics of amide-based materials, primarily the facile nature of the reversibility of the hydrogen storage reaction, as a model for the development and optimisation of solid-state hydrogen stores. The study of the relationship between the crystal structures of the relevant materials and their hydrogen storage properties through in situ X-ray and neutron powder diffraction measurements is reported for the lithium amide - lithium hydride (Li-N-H) hydrogen store. These investigations provide strong evidence for ionic mobility as the basis of reversible hydrogen storage in the Li-N-H system. The hydrogen storage and release reactions are seen to progress through a continuum of non-stoichiometric states, a transformation which is facilitated by its topotactic nature. The structural and energetic properties of these non-stoichiometric phases are reported, showing that they are intrinsically disordered and thermodynamically unstable relative to their parent structures. The study of the behaviour of the Li-N-H system is extended to many tens of hydrogenation-dehydrogenation cycles to examine practical performance, confirming the mechanism of capacity loss through the formation of parasitic lithium hydride, and showing that the addition of nitrogen improves the cycling lifetime of the system. An unexplored aspect of light metal amide chemistry is also presented, where the hydrogen storage and release reactions of sodium amide are performed simultaneously. Together, these reactions effect the chemical decomposition of ammonia. Ammonia is a high energy density liquid hydrogen carrier which has been largely overlooked, partly due to the difficulty extracting its stored hydrogen. This work demonstrates a new method of ammonia decomposition which gives comparable performance to the expensive rare-metal catalysts which are currently used for the productions of high-purity hydrogen. A survey of the ammonia decomposition efficiency of a number of light metal amides and imides is presented, showing that it is not only amides which decompose into their constituent elements (such as sodium amide) which are active in ammonia decomposition, but also imide-forming amides. Indeed, imides and imide-forming amides are shown to be advantageous from the perspective of containing the catalyst material. Neutron diffraction and isotope exchange measurements provide some initial insights into the mechanism of reaction, identifying clear avenues for development of these systems, and inviting further discussion of the potential of ammonia as a sustainable energy vector.